New records of lichenized fungi for Antarctica - Mehmet Gökhan Halici; Merve Kahraman; Osman Osmanoğlu; Milos Bartak (Polish Polar Research, 2021)
Three lichenized fungal species collected from James Ross Island (eastern coast of Antarctic Peninsula): Cladonia acuminata (Ach.) Norrl., Rhizocarpon pusillum Runemark and Rhizoplaca parilis S.D. Leav., Fern.-Mend., Lumbsch, Sohrabi et St. Clair are reported from Antarctica for the first time. Detailed morphological and anatomical properties of these species along with photographes based on Antarctic specimens are provided here. In addition, the nrITS gene regions of the selected specimens are studied and the phylogenetic positions of the species are discussed. The nrITS data for Rhizocarpon pusillum is provided for the first time. According to our studies the lichen biodiversity of the Antarctic is still poorly known and molecular studies are very important in order to present the correct lichen biodiversity of Antarctica.